Compressive strength of lightweight foamed concrete bricks with different size of hollow under different curing regime - Nur Afirah, Kamalrulzaman (2014)
Lightweight foamed concrete is a unique product of construction material that has been used in the construction of the building. The usage of lightweight foamed concrete as the bricks was nof widely used in Malaysia. Cost savings in using mortar for bricklaying can be reduced because mortar just pasted to the face of the hollow brick alone compared with solid brick that need to paste mortar around the face. Hollow concrete brick are slow to absorb heat and with the using of this brick is suitable for a living due to the nature of concrete that is not hot plus empty space in the brick and heat will flow to avoid the heat trapped inside it. The purpose of this study is to determine the effect of different size of the hollow to compressive strength of foamed concrete bricks and also to determine the compressive strength of hollow foamed concrete bricks under different curing regimes. In this study, the density of the lightweight foamed concrete used is 1600 kg/M3 while the size of the brick used is 215 x 102.5 x 65 mm. Sample A represent the solid brick while Sample B, Sample C and Sample D were the bricks with hollow size 55 x 55 mm, 60 x 60 mm and 65 x 65 mm respectively. Eighty samples of bricks with different hollow sizes have prepared. Under the bed position, the compressive strength was 30 - 56% decreased with the increasing size of hollow while for stretcher was 52 - 76%. The compressive strength in both stretcher and bed position under water-curing regime was 1 - 20% higher compared to samples under air-curing regime.